1991
DOI: 10.1002/yea.320070707
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall glucomannoproteins of Saccharomyces cerevisiae mnn9

Abstract: Mannoproteins were isolated from Saccharomyces cerevisiae mnn9 mutant cell walls by laminarinase digestion and purified by affinity and anion-exchange chromatography. The purified mannoprotein fraction contained three predominant proteins with molecular masses of 300 kDa, 220 kDa and 160 kDa. These compounds were absent in an SDS extract of cell walls or in a hot-citrate extract of mnn9 cells. The carbohydrate part of the purified mannoproteins consisted of (N-acetyl)glucosamine, mannose and glucose in a molar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 39 publications
2
73
0
Order By: Relevance
“…Cultures were grown to an OD,,, nm of 2.0. Cell walls were isolated as in [2], boiled in the presence of SDS, EDTA and /I-mercaptoethanol to obtain detergent extracts as in [7] and subsequently digested with laminarinase to obtain B-1,3glucanase extracts as in [2]. Proteins present in the culture fluid were precipitated using deoxycholate [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures were grown to an OD,,, nm of 2.0. Cell walls were isolated as in [2], boiled in the presence of SDS, EDTA and /I-mercaptoethanol to obtain detergent extracts as in [7] and subsequently digested with laminarinase to obtain B-1,3glucanase extracts as in [2]. Proteins present in the culture fluid were precipitated using deoxycholate [8].…”
Section: Methodsmentioning
confidence: 99%
“…We recently demonstrated that several /I-1,3-glucanase-extractable wall proteins are covalently linked to a /I-1,6-glucan [2,3]. This raised the question whether this type of side-chain is involved in anchoring glucanaseextractable mannoproteins in the cell wall.…”
Section: Introductionmentioning
confidence: 99%
“…Van Rinsum et al (1991) isolated a carbohydrate chain consisting of glucosamine, mannose and~-glycosydicallylinked glucose fronl glucanase-extracted cell wall proteins in a molar ratio of 1: 17: 18. This -1 ,6-glucan chain is involved in cell wall anchorage (Kapteyn et a1., 1996).…”
Section: Glucanase-extractable Mannoproteinsmentioning
confidence: 99%
“…Glucan and chitin in Schizophyllum cumnzune are connected by covalent bridges (Sonnenberg et al, 1982;Wessels et al, 1983), and linkages between mannoproteins and glucose molecules (glucans) have been suggested in Sacch. cerevisiae (van Rinsum et al, 1991). However, the nature of the linkages is still a matter of speculation.…”
Section: Introductionmentioning
confidence: 99%